Effects Of Organic Amendmentson Methane Emission And Yield Of Rice (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The effect of FYM, poultry litter, livestock manure, biogas slurry, vermi-compost and municipal solid waste (MSW) combined with NPK.was assessed on emission of CH4 and yield of rice. The highest amount of CH4 emission (815.04) kg ha-1 season'1 was from MSW followed by (702.96 kg CH4 ha'1 season'1) from livestock manure. The lowest (365.14 kg CH4 ha'1 season'1) was produced in control treatment. The increasing trend of seasonal CH4 emission was 55.20, 48.06, 35.71, 33.88, 21.13 and 17.57% respectively due to organic amenments against the control. The highest number of panicle hill'1 (14.38), grain panicle'1 (160.67), yield of grain (5.47tha'1) and straw weight (4.56 t ha'1) was observed due to application of FYM, vermicompost and poultry litter respectively. The highest percentage of harvest index and ripened grains (55.363 and 93.41) was found in biogas slurry and poultry litter treated plots and the lowest percentage (52.878 and 85.88) was with vermicompost and biogas slurry correspondingly. The highest Eh value (- 252.0 mV) was found in MSW and the lowest value was observed in poultry litter. Result suggests that combined use of inorganic fertilizer and organic amendments caused highest yield of rice with less CH4 emission.Asiat. Soc. Bangladesh, Sci. 41(2): 263-270, December 2015